Evaluating the national digitization project of the National Science Foundation Sri Lanka: Achievements, challenges, and library perspectives - Priyadarshani, N.A.H.; Gamage, Ruwan (University of Colombo, 2025)
This study evaluates the National Digitization Project (NDP) of the National Science Foundation (NSF) of Sri Lanka, which was implemented from 2011 to 2018, using a survey administered in 2025, after 7 years of implementation. The objective of NDP was to enhance accessibility, visibility, and long-term preservation through the establishment of a nationwide network of institutional repositories. Twenty five (25) university, research, statutory, and government libraries participated in the project. NSF supported digitization of 3 million pages of content from annual reports, journals, conference proceedings, theses and other publications selected by participating libraries. Main criteria for selection were institutional priority, scientific relevance and rarity. The heads of all 25 libraries were included in the questionnaire-based survey. Twenty-one (21) responded. The nature of support provided by NSF, current state, usage, and challenges faced by them were analyzed. To date, 17 (84%) repositories remain active. Among them, four (4) are at low to moderate usage. Participants acknowledged the NSF’s significant role in providing technical support and training. They strongly agreed that the project encouraged establishing a digital culture and enabling collaboration among institutions. Persistent challenges were insufficient skilled staff (52%), limited ongoing training opportunities (42%), copyright concerns (38%), and lack of infrastructure (33%). To address these issues, the study recommends providing continuous training programmes, sustained technical support, as well as amending institutional repository policies, and executing targeted promotional campaigns. In conclusion, digitization should not be viewed as a one-time initiative but as a continuous and sustained process. These are essential to maximize the long-term impact of the NDP to ensure the sustainable digital preservation of Sri Lanka’s scientific and technical literature.
Keywords: National Digitization Project; Institutional repositories; Sustainability of projects